Barriers to Palliative Care in Pediatric Oncology in Switzerland: A Focus Group Study. (January 2020) - Rost, Michael; De Clercq, Eva; Rakic, Milenko; Wangmo, Tenzin; Elger, Bernice
Introduction: For children with cancer, early integration of pediatric palliative care in conjunction with curative treatments is recommended. In Switzerland, pediatric palliative care is mostly provided by an interdisciplinary primary oncology team that is mainly composed of nurses. However, only a small fraction of children receive pediatric palliative care and only a minority of them in a timely manner. The main aim was to identify barriers to the provision of pediatric palliative care in Swiss pediatric oncology.Method: This qualitative study consisted of five focus groups. In total, 29 pediatric oncology providers participated (13 nurses, 11 physicians, 4 psycho-oncologists, 1 social worker). Data were analyzed employing applied thematic analysis.Results: Analysis revealed eleven barriers: lack of financial resources, lack of prejob education regarding pediatric palliative care, lack of awareness in politics and policy making, absence of a well-established nationwide bridging care system, insufficient psychosocial and professional supervision for staff, understaffing, inadequate infrastructure of hospitals, asymmetry of factual and emotional knowledge between parents and providers, cultural aspects, irrational parental hopes, and "the unspoken."Discussion: Awareness should be raised for pediatric palliative care (in particular in demarcation from palliative care in adults) among politics and policy makers which could lead to increased financial resources that, in turn, could be used to improve bridging care, hospital's infrastructure, and team support. More flexibility for care determining factors is needed, for example, with respect to convening team meetings, short-termed staffing, and reimbursement at the interface between inpatient and outpatient services.